2013
DOI: 10.1088/0004-637x/778/2/159
|View full text |Cite
|
Sign up to set email alerts
|

Dusty Supernovae Running the Thermodynamics of the Matter Reinserted Within Young and Massive Super Stellar Clusters

Abstract: Following the observational and theoretical evidence that points at core-collapse supernovae (SNe) as major producers of dust, here we calculate the hydrodynamics of the matter reinserted within young and massive super stellar clusters under the assumption of gas and dust radiative cooling. The large SN rate expected in massive clusters allows for a continuous replenishment of dust immersed in the high temperature thermalized reinserted matter and warrants a stationary presence of dust within the cluster volum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…The process of mass accumulation in star clusters with a bimodal solution was explored by Wünsch et al (2008) who ran 2D hydrodynamic simulations and found that parcels of the hot gas below the stagnation radius cool rapidly from ∼ 10 7 K down to the minimum allowed temperature 10 4 K (motivated by the assumption that the gas is ionized by stellar radiation) and are subsequently compressed by the surrounding hot gas until they reach pressure equilibrium as dense warm clumps. The bimodal solution was further studied by Tenorio-Tagle et al (2010) who estimated the shapes of recombination line profiles from 2D simulation, Silich et al (2010) who applied it to high-redshift SCUBA galaxies with extremely high star formation rates, Hueyotl-Zahuantitla et al (2010 who applied it to galactic nuclear star clusters, Wünsch et al (2011) who calculated the time evolution of clusters evolving in the bimodal regime for the whole period of the existence of massive stars, and Tenorio-Tagle et al (2013) who included cooling due to dust produced by supernovae.…”
Section: Introductionmentioning
confidence: 99%
“…The process of mass accumulation in star clusters with a bimodal solution was explored by Wünsch et al (2008) who ran 2D hydrodynamic simulations and found that parcels of the hot gas below the stagnation radius cool rapidly from ∼ 10 7 K down to the minimum allowed temperature 10 4 K (motivated by the assumption that the gas is ionized by stellar radiation) and are subsequently compressed by the surrounding hot gas until they reach pressure equilibrium as dense warm clumps. The bimodal solution was further studied by Tenorio-Tagle et al (2010) who estimated the shapes of recombination line profiles from 2D simulation, Silich et al (2010) who applied it to high-redshift SCUBA galaxies with extremely high star formation rates, Hueyotl-Zahuantitla et al (2010 who applied it to galactic nuclear star clusters, Wünsch et al (2011) who calculated the time evolution of clusters evolving in the bimodal regime for the whole period of the existence of massive stars, and Tenorio-Tagle et al (2013) who included cooling due to dust produced by supernovae.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained here can contribute to the understanding of dust formation and evolution at early stages of the Universe, when most of the dust grains are expected to be formed in the supernovae ejecta (e.g. Todini & Ferrara 2001, Marchenko 2006, Bianchi & Schneider 2007, Tenorio-Tagle et al 2013). Indeed, recent calculations suggest that in low ambient gas densities (n0 < 100 cm −3 ), just a small fraction (about 10% − 20%) of dust grains could survive crossing the reverse shock (e.g.…”
Section: Summary and Discussionmentioning
confidence: 79%
“…The above relations yield a shocked gas temperature T S = 5.2 × 10 7 K and a shocked gas density n S ∼ 2×10 3 cm −3 . These, together with the value of the cooling rate, Λ ∼ 10 −20 erg cm 3 s −1 (see Figure 2 of Tenorio-Tagle et al 2013) lead to the cooling time:…”
Section: The Broad Emission Linesmentioning
confidence: 94%